Physiology and Pathophysiology of Compensatory Adaptations of a Solitary Functioning Kidney - McArdle, Zoe; Schreuder, Michiel F.; Moritz, Karen M.; Denton, Kate M.; Singh, Reetu R. (Frontiers in Physiology, 2020)
Children born with a solitary functioning kidney (SFK) have an increased risk of hypertension and renal disease from early in adulthood. In response to a reduction in renal mass, the remaining kidney undergoes compensatory renal growth. This is associated with both an increase in size of the renal tubules and the glomeruli and an increase in single nephron glomerular filtration rate (SNGFR). The compensatory hypertrophy and increase in filtration at the level of the individual nephron results in normalization of total glomerular filtration rate (GFR). However, over time these same compensatory mechanisms may contribute to renal injury and hypertension. Indeed, approximately 50% of children born with a SFK develop hypertension by the age of 18 and 20-40% require dialysis by the age of 30. The mechanisms that result in renal injury are only partly understood, and early biomarkers that distinguish those at an elevated risk of renal injury are needed. This review will outline the compensatory adaptations to a SFK, and outline how these adaptations may contribute to renal injury and hypertension later in life. These will be based largely on the mechanisms we have identified from our studies in an ovine model of SFK, that implicate the renal nitric oxide system, the renin angiotensin system and the renal nerves to renal disease and hypertension associated with SFK. This discussion will also evaluate current, and speculate on next generation, prognostic factors that may predict those children at a higher risk of future renal disease and hypertension.